Re-Thinking The Consumerism Phenomenon in The Liberalist-Capitalist Economic System: In A Search of an Islamic Consumerism Model - Mohd Shukri Hanapi (Yayasan Rumah Peneleh, 2019)
In the liberalist-capitalist economic system widely applied presently, one who spends his income to maximise material utility is presumed to be something that is rational and encouraged. This is because maximum consumption of material utility is a measure of progress. However, maximising utility consumption to achieve material satisfaction could cause negative effects, especially serious debt problems and bankruptcy. This is due to consumers spending their income to maximise material satisfaction beyond their capability; thus, making them go into debt. The issue is as Muslim consumers, what is the actual level of consumption that should be practiced? Is the measurement also based on the maximum consumption of utilities such as in the liberalist-capitalist economic system mainly practiced today or is there a specific measurement that offers a unique form of consumption? In relation to this issue, this paper aimed to re-thin the consumerism phenomenon in the liberalist-capitalist economic system and explore an Islamic consumerism model, which is otherwise known as wasatiyyah-consumerism. In order to achieve this objective, this study had only explored ideas related to the wasatiyyah-consumerism model. The study found that the wasatiyyah-consumerism model applied the tawhid (monotheism) philosophy, a level of consumerism rooted in the maqasid al-syari‘ah component and aimed at achieving the blessings of Allah SWT.